The efficacy of Canva as a digital tool for enhancing student learning in multimedia interactive subjects - Zainal Abidin, Saffa Raihan; Jalaluddin, Nurkhuzaimah Fazreen; Ismail, Nor Zalina; Zainal, Mohd Azim (Penerbit UiTM (UiTM Press), 2025)
This study investigates the effectiveness of Canva as a digital tool for enhancing student learning in multimedia and interactive subjects. Drawing on data from 125 university students across four classes, the research explores Canva’s impact on student comprehension, engagement, and note-taking performance. Participants engaged in peer-teaching activities using Canva to create multimedia-based educational content, which was subsequently evaluated using rubrics and post-activity surveys. The results indicate that students reported high levels of perceived engagement, understanding, and collaborative effectiveness when using Canva compared to traditional tools such as Microsoft PowerPoint. The platform’s intuitive interface and versatile design features were particularly well-received, contributing to students’ preference for Canva in educational contexts. Overall, the findings suggest that Canva can serve as a valuable pedagogical resource in visually oriented learning environments. The study recommends further exploration of its implementation across diverse subjects and educational settings to maximise its educational impact.